Leadership sharing in maternity emergency teams: a retrospective cohort study in simulation. (7th February 2019) - Janssens, Sarah; Simon, Robert; Barwick, Stephanie; Beckmann, Michael; Marshall, Stuart
Abstract : Background: Shared leadership is associated with improved team performance in many domains, but little is understood about how leadership is shared spontaneously in maternity emergency teams, and if it is associated with improved team performance. Methods: A video analysis study of multidisciplinary teams attending a maternity emergency management course was performed at a simulation centre colocated with a tertiary maternity hospital. Sixteen teams responding to a simulated postpartum haemorrhage were analysed between November 2016 and November 2017. Videos were transcribed, and utterances coded for leadership type using a coding system developed a priori . Distribution of leadership utterances between team members was calculated using the Gini coefficient. Teamwork was assessed using validated tools and clinical performance was assessed by time to perform a critical intervention and a checklist of required tasks. Results: There was a significant sharing of leadership functions across the team despite the traditional recommendation for a singular leader, with the dominant leader only accounting for 58% of leadership utterances. There was no significant difference in Auckland Team Assessment Tool scores between high and low leadership sharing teams (5.02 vs 4.96, p=0.574). Time to critical intervention was shorter in low leadership sharing teams (193 s vs 312 s, p=0.018) but checklist completion did not differ significantly. Teams with better clinical performance had fewer leadership utterances beyond the dominant two leaders compared with poorer performing teams. Conclusions: Leadership is spontaneously shared in maternity emergency teams despite the recommendation for singular leadership. Spontaneous leadership emerging from multiple team members does not appear to be associated with the improvements in team performance seen in other domains.